Preoperative ultrasound risk factors for peripartum hysterectomy among PAS suspected pregnancies - Lulu Wang; Tianjiao Liu; Yang Yang; Yalan Li; Li Xiao; Xin Li; Sumei Wei (BMC Pregnancy and Childbirth)
Abstract Objective This study aimed to identify risk factors for peripartum hysterectomy among pregnancies complicated by suspected Placenta Accreta Spectrum (PAS) in preoperative obstetric imaging screening. Methods Data were retrospectively extracted from the Longitudinal Placenta Accreta Spectrum Study (LoPASS), covering pregnancies with PAS from January 2018 to March 2023 at our institute. Patients were divided into Control and Hysterectomy groups based on whether they underwent hysterectomy. Sociodemographic, obstetric, and clinical characteristics were compared between the groups. Multivariate logistic regression analysis was performed on the characteristics with statistical significance to explore risk factors for peripartum hysterectomy. Results Among 523 pregnancies with suspected PAS, 20 underwent hysterectomy. The Hysterectomy group had a significantly higher mean age (34.50 ± 5.05 vs. 31.66 ± 4.43 years, p = 0.005) and pre-pregnancy BMI (26.35 ± 3.27 vs. 23.84 ± 3.99, p = 0.006). The Hysterectomy group also had a higher proportion of patients with more than 2 gravidities (100% vs. 61.6%, p = 0.022) and multiple parities (90.0% vs. 39.9%, p < 0.001). Higher percentages of placenta percreta (90.0% vs. 28.2%, p < 0.001), placenta attaching to the anterior uterine wall (57.9% vs. 31.8%, p = 0.033), and higher PAS ultrasonographic scores (11.78 ± 2.68 vs. 6.79 ± 2.77, p < 0.001) were observed in the Hysterectomy group. Perioperative outcomes revealed significantly longer surgical durations (171.90 ± 49.27 vs. 53.46 ± 24.41 min, p < 0.001) and higher rates of preterm birth (100.0% vs. 55.3%, p < 0.001). Intraoperative blood loss was also substantially greater in the Hysterectomy group (2695.00 ± 1241.17 ml vs. 764.31 ± 385.10 ml, p < 0.001). Variables significantly associated with increased peripartum hysterectomy risk included prior cesarean sections (OR = 1.44, p = 0.048), placenta attaching to the anterior uterine wall (OR = 0.73, p = 0.015), placenta completely covering the uterine incision (OR = 1.27, p = 0.035), gestational hypertensive disorder (OR = 1.69, p = 0.042), placenta percreta (OR = 2.31, p = 0.032), and PAS ultrasonographic score higher than 10 (OR = 2.71, p = 0.008). Conclusion Most of ultrasound PAS scoring subitems were significantly higher in Hysterectomy group. Cesarean deliveries, placental positioning on the anterior uterine wall, GHD, types of PAS, and ultrasound PAS score higher than 10 predicts peripartum hysterectomy, highlighting the importance of early, timely, and consistent monitoring of the placenta using obstetric ultrasound in pregnancies with suspected PAS. Trial registration ChiCTR2100052428, October 26th, 2021.